Cover page. Issue 7 (7th July 2021) - Oda, Yukari; Mori, Gentaro; Honma, Shinya; Ito, Taichi; Iijima, Toshikazu; Yajima, Yasutomo
Abstract : COVER ILLUSTRATION: The cover image is based on the Original Article Marginal bone loss and the risk indicators of fixed screwretained implant‐supported prostheses and fixed telescopic‐retained implant‐supported prostheses in full arch by Yukari Oda et al., https://doi.org/10.1111/clr.13750 .